Preparation of Pre-Confluent Retinal Cells Increases Graft Viability In Vitro and In Vivo: A Mouse Model - O'FARRELLY, CLIONA (My University, 2011)
Purpose: Graft failure remains an obstacle to experimental subretinal cell transplantation. A key step is preparing a viable graft, as high levels of necrosis and apoptosis increase the risk of graft failure. Retinal grafts are commonly harvested from cell cultures. We termed the graft preparation procedure ?transplant conditions? (TC). We hypothesized that culture conditions influenced graft viability, and investigated whether viability decreased following TC using a mouse retinal pigment epithelial (RPE) cell line, DH01. Methods: Cell viability was assessed by trypan blue exclusion. Levels of apoptosis and necrosis in vitro were determined by flow cytometry for annexin V and propidium iodide and Western blot analysis for the pro- and cleaved forms of caspases 3 and 7. Graft viability in vivo was established by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) and cleaved caspase 3 immunolabeling of subretinal allografts. Results: Pre-confluent cultures had significantly less nonviable cells than post-confluent cultures (6.6%?0.8% vs. 13.1%?0.9%, p<0.01). Cell viability in either group was not altered significantly following TC. Caspases 3 and 7 were not altered by levels of confluence or following TC. Pre-confluent cultures had low levels of apoptosis/necrosis (5.6%?1.1%) that did not increase following TC (4.8%?0.5%). However, culturing beyond confluence led to progressively increasing levels of apoptosis and necrosis (up to 16.5%?0.9%). Allografts prepared from post-confluent cultures had significantly more TUNEL-positive cells 3 hours post-operatively than grafts of pre-confluent cells (12.7%?3.1% vs. 4.5%?1.4%, p<0.001). Subretinal grafts of post-confluent cells also had significantly higher rates of cleaved caspase 3 than pre-confluent grafts (20.2%?4.3% vs. 7.8%?1.8%, p<0.001). Conclusion: Pre-confluent cells should be used to maximize graft cell viability.
PUBLISHED
Keywords: Ophthalmology; subretinal cell transplantation; Immunology, Inflammation & Infection